2017
DOI: 10.2196/publichealth.7047
|View full text |Cite
|
Sign up to set email alerts
|

Body Weight Misperception and Dissatisfaction Among Overweight and Obese Adult Nigerians

Abstract: BackgroundThe increase in the prevalence of overweight and obesity in low- and medium-income countries has a negative impact on overall health. Correct perception of one’s body weight is a step in seeking healthy help toward weight reduction in overweight and obese individuals.ObjectiveThis study was carried out to assess the body weight misperception and dissatisfaction among overweight and obese adults in an urban African setting.MethodsThis study was part of a larger cross-sectional study that was designed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
5

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 27 publications
0
8
5
Order By: Relevance
“…This age difference may suggest that younger individuals have more opportunities to be aware of their own body weight compared to older individuals [58,59]. However, our finding contradicts with findings in Nigeria, where the underestimation of weight was associated with being in younger age group, female gender, and employment status [57]. Whatever the pattern of association, given the fundamental importance of body weight self-awareness in CVD prevention programs, it is important to understand how such a misperception of body weight arose in the SSA context.…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…This age difference may suggest that younger individuals have more opportunities to be aware of their own body weight compared to older individuals [58,59]. However, our finding contradicts with findings in Nigeria, where the underestimation of weight was associated with being in younger age group, female gender, and employment status [57]. Whatever the pattern of association, given the fundamental importance of body weight self-awareness in CVD prevention programs, it is important to understand how such a misperception of body weight arose in the SSA context.…”
Section: Discussioncontrasting
confidence: 81%
“…Very limited opportunities to actually measure body weight might contribute to misperceptions about body weight. Underestimation of body weight has been recently reported in other LMICs such as Sri Lanka, Pakistan, and Nigeria [5759].…”
Section: Discussionmentioning
confidence: 99%
“…Mothers who preferred an overweight silhouette for their child said that a larger size shows that the child is healthy and strong. Mothers who wanted their child to have a smaller body size (N = 28) listed foods similar to those who wanted their child to maintain or gain weight, such as porridge (54%); fruit, nsima and fizzy drinks (36%); sweetened yogurt (29%); meat and green leafy vegetables (25%); groundnuts (18%); and milk and rice (14%; was higher than in studies in Nigeria, Kenya, the Seychelles, South Africa, Tanzania and Zambia, some of which included both men and women or only overweight/obese adults (Akindele, Phillips, Igumbor, & Useh, 2017;Devanathan et al, 2013;Ettarh, Van de Vijver, Oti, & Kyobutungi, 2013;Muhihi et al, 2012;Tateyama et al, 2018;Yepes et al, 2015). In the present study, the percentage of women who correctly estimated their current size did not differ significantly by measured weight status, in contrast to some other studies, which found that overweight participants were more likely than normal weight participants to underestimate their weight status (Muhihi et al, 2012;Tateyama et al, 2018).…”
Section: Child Body Size Perceptions and Preferencesmentioning
confidence: 81%
“…In the context of urbanization in Africa, which is characterized by a rural exodus and intensification of internal migration, new migrants are progressively exposed to NCDs (Oyebode et al, 2015). Nevertheless, their traditional preference for stoutness (overweight/obesity) seems to remain in these obesogenic areas, as observed in Ghana, Cameroon and Nigeria (Appiah et al, 2016;Akindele et al, 2017;Cohen et al, 2017). Indeed, the propensity towards stoutness is strengthened during the internal migration, particularly as this paradigm is viewed as a sign of successful integration into the modern urban lifestyle associated with abundance.…”
Section: Introductionmentioning
confidence: 99%